STRATEGI MENGELOLA KETIDAKSEIMBANGAN SUPPLY AND DEMAND PADA INDUSTRI PERHOTELAN DI SOLO RAYA* - Purnomo, Budi; Adji, MSU (Benefit: Jurnal Manajemen dan Bisnis, 2015)
Since 2011 hotel industry in Solo Raya has very significant demand and supply imbalance in the fields of room occupancy rate, human resources and finance. So, this research is intended to find strategies to manage the supply and demand imbalance along with long term solutions to overcome these conditions. This process evaluation study is presented to evaluate the implementation of ongoing programs and policies in order to improve their qualities and to asses if they are successfull or failed (Edison, 2009). Several methods of data collection are documentation, observation and field notes and interviews with questionnaire. Subjects of research are whole members of Indonesia Hotel & Restaurant Association (PHRI) Surakarta which are classified as star and nonstar hotels, local government officers and tourism service providers. The research findings show that: (1) to increase the room occupancy rate is by increasing the number of guests through promoting special packages offering customized solutions, instead of reducing the number of existing hotels; (2) during low seasons, optimize in-house trainings to improve human resources with expected competencies, entrepreneur souls and risk-taking; and (3) implement a comprehensive efficiency program to maintain healthy financial companies. The research findings imply the needs of political will from government which supports tourism sector to create âsome sugarâ(tourist attractions) in Solo Raya that will be consumed by âantsâ (tourists).Â